The Transformation of Labor Party Immigration Policy, 1901–1945. Issue 4 (1st October 2016) - Holbrook, Carolyn
ABSTRACT: The Commonwealth Labor government's introduction of a program of mass immigration after the Second World War was a pivotal moment in the nation's history. The program itself and the experiences of those who settled in Australia have been studied closely by historians and social scientists. Less attention has been given to the fact that the postwar policy represented a transformation of Labor's traditional attitude to immigration. Since its foundation in the 1890s, the Australian Labor Party had been suspicious of immigration and opposed to programs of assisted immigration on the basis that migrant labour threatened the wages and conditions of Australian workers. This article traces Labor's attitudes to migration before the Second World War and shows how economic and security exigencies compelled the party to repudiate its decades-long opposition to assisted immigration. The article suggests that the reason that the postwar immigration program does not receive greater prominence in histories of the Labor Party is because the policy and its chief architect, Arthur Calwell, are diminished by their association with the White Australia policy.